A Robust Operation: Resettling, Security, and Development in Late Colonial Angola (1960s-1970s) - Jerónimo, Miguel Bandeira (2020)
The forced removal and resettlement of population was a main feature of late European colonialism, in Africa and elsewhere. Both were crucial to the formulation and enactment of securitarian projects and developmental schemes, and to their recurrent intersection and close interdependence. The repertoires of repressive developmentalism—the shaping of development strategies by securitarian concerns and the contamination of schemes of security by socioeconomic rationales—were diverse, inspiring the various authorities and guiding many specific operations on the ground. This text provides one telling example of these repertoires, the Operação Robusta (1969–1974), which entailed the forced removal of thousands of men, women, and children from the district of North Cuanza to the district of Zaire (both in the north of Angola, under Portuguese rule, and in the middle of an armed conflict that started in 1961), and was seen as a model for similar actions. Assessing the drives and the prospects associated with the operation, this text also addresses its violent dynamics and effects, namely the substantial separation of families, the meagre provision of welfare, and the intense processes of land expropriation.